Pendidikan Kesehatan tentang Tumbuh Kembang Remaja dan Bahaya Rokok bagi Kesehatan Remaja di SMK Baitussalam Kota Pekalongan - Pedvin Ratna Meikawati; Hilda Prajayanti (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2020)
Adolescence is a transition period from childhood to adulthood and there are some physical changes that are fast matching with adults, but emotions do not necessarily follow physical development. Adolescence is a critical age. Biologically the reproductive organs of adolescents have reached maturity (have experienced wet dreams for men and menstruation for women). This means they are able to be sexually active. This period is a potential period but it is forbidden to actualize the sexual potential along with the early maturity of the reproductive organs (under fifteen years) and the increase in the average age of first marriage (over 20 years). They are required to control their sex drive during this period. Control like this is indeed very necessary. From the religious point of view, this control is interpreted as a form of piety in God. While from a reproductive health perspective, avoiding premarital sex is the best way to prevent the transmission of sexually transmitted infections and unwanted pregnancy. Indonesia is in the fifth ranks among the countries with the highest levels of tobacco consumption in the world. WHO says 1 in 10 deaths in adults is caused by smoking. The smoking habit in students is caused due to misunderstanding of information, the influence of advertising and the influence of friends. Smoking behavior is related to knowledge, one's attitude towards cigarettes and education. The hope is that given information and health education about adolescent growth and development and the dangers of smoking to adolescents can increase knowledge before and after socialization. Pretest and posttest were carried out to find out the teenager's knowledge. The results obtained are an increase in adolescent vocational high school Baitussalam Pekalongan City after counseling about adolescent growth and development and the dangers of smoking in adolescents.